1996
DOI: 10.1021/bi961584d
|View full text |Cite
|
Sign up to set email alerts
|

Role for Pro-13 in Directing High-Affinity Binding of Anthopleurin B to the Voltage-Sensitive Sodium Channel

Abstract: Anthopleurin A (ApA) and B (ApB) are 49-amino acid polypeptide toxins from the Pacific sea anemone Anthopleura xanthogrammica that interfere with inactivation of voltage-gated sodium channels. ApA, which differs from ApB in seven of the 49 amino acids, displays markedly enhanced isoform selectivity compared with ApB, acting preferentially on cardiac over neuronal sodium channels. Previous studies in this lab have indicated the importance of two unique charged residues in ApB, Arg-12 and Lys-49, in this toxin's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…Residues Arg-14, His-34, His-39, and Lys-48 have produced only small effects on toxin affinity when neutralized (25, 39) and so were relatively poor candidates for interacting with Asp-1612; similarly, short Nterminal extensions of the toxin have no measurable effect on its affinity (21,40). We tested toxin ApB H39A as a representative of this group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Residues Arg-14, His-34, His-39, and Lys-48 have produced only small effects on toxin affinity when neutralized (25, 39) and so were relatively poor candidates for interacting with Asp-1612; similarly, short Nterminal extensions of the toxin have no measurable effect on its affinity (21,40). We tested toxin ApB H39A as a representative of this group.…”
Section: Resultsmentioning
confidence: 99%
“…Residues Arg-12 and Lys-49 are known to have a significant and cooperative effect on toxin affinity (23) but are not conserved among all anemone toxins; in particular, they are neutral in ATX-II, the toxin tested by Rogers and colleagues (18). We tested these residues by using toxin ApA, which has neutral residues at both positions (in addition to several more conservative differences which have been shown to have only minor effects on toxin affinity) (22,40). The remaining residue, Lys-37, significantly decreased the affinity of ApB when neutralized (25) and is also conserved among a number of anemone toxins.…”
Section: Resultsmentioning
confidence: 99%
“…All ApB mutants were assayed either on cardiac rNa v 1.5 and brain rNa v 1.2a channels transiently expressed in HEK cells, or mammalian cell lines that constitutively express these channels among a minority of other channel subtypes. These studies have suggested a bioactive role for Arg-12, Asn-16, Leu-18, Ser-19, Trp-33, Lys-37 and Lys-49, of which most bioactive residues were associated with the Arg-14 loop and with the substitutions of Leu-18 having the strongest effect on ApB activity (Blumenthal and Seibert, 2003; Khera and Blumenthal, 1996; Dias-Kadambi et al, 1996a; Dias-Kadambi et al, 1996b; Kelso et al, 1996; Seibert et al, 2004; Fig. 2 and Fig.…”
Section: The Bioactive Surfaces Of Sea Anemone Toxinsmentioning
confidence: 93%
“…However, these results were contradicted in later elecrophysiological studies showing preference of both ApA and ApB for cardiac channels (Khera et al, 1995). Attempts to ameliorate improve by site-directed mutagenesis ApB selectivity to the rat cardiac sodium channel rNa v 1.5, while retaining the original potency, had limited success (Khera and Blumenthal, 1996; Dias-Kadambi et al, 1996a; Dias-Kadambi et al, 1996b; Kelso et al, 1996). Characterization of Av2 effects on various heterologously expressed mammalian Na v s revealed that it was five times more active at hNa v 1.5 (human cardiac channel subtype) than at rNa v 1.4 (rat skeletal muscle channel subtype) (Chahine et al, 1996).…”
Section: The Selectivity Of Sea Anemone Toxinsmentioning
confidence: 99%
“…At low concentrations (< 40 μg/kg) these toxins, after in vivo intravenous, intracisternal (mammals) or intramuscular (crustaceans) injections, induce severe toxic syndromes including paralysis, general hyperexcitability, cardiac disorders, convulsions and death (Alsen et al 1978;Schweitz 1984). These toxins interact with a large variety of excitable cells including neurons, cardiac and skeletal muscle cells (Abita et al 1977;Bergman et al 1976;Kelso et al 1996;Renaud et al 1986;Romey et al 1976;Shibata et al 1976). In cardiac tissues they induce positive inotropic effects, arrhythmias or cell fibrillation (Hanck and Sheets 1995;Khera et al 1995;Reimer et al 1985;Renaud et al 1986;Shibata et al 1976).…”
Section: The First Isolated Sea Anemone Toxins Affect Voltage-gated Smentioning
confidence: 99%